Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/17538068.2015.1126995
|View full text |Cite
|
Sign up to set email alerts
|

A pilot test of the acceptability and efficacy of narrative and non-narrative health education materials in a low health literacy population

Abstract: Although entertainment-education narratives are increasingly being used to communicate health information to a diversity of populations, there is limited evidence examining the use of narrative health education videos in low compared with adequate health literacy populations. There are also very few studies directly comparing narrative materials to more traditional, non-narrative materials. Because individuals with low health literacy are less likely than those with adequate health literacy to benefit from hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 50 publications
2
43
1
Order By: Relevance
“…The use of narratives is emerging as a strategy to educate, persuade, and prompt health behavior change. Some previous studies reported that delivery of health information through the use of narratives was intrinsically persuasive (Kreuter et al, 2007;Kreuter et al, 2010;Dahlstrom, 2014) and more acceptable for patients with low and adequate health literacy (Moran et al, 2016) and populations that had a strong oral tradition (Hinyard and Kreuter, 2007), such as Indonesia. It is noteworthy to mention that PERANTARA contained information about both medical and psychosocial issues related to BC symptoms and diagnosis procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The use of narratives is emerging as a strategy to educate, persuade, and prompt health behavior change. Some previous studies reported that delivery of health information through the use of narratives was intrinsically persuasive (Kreuter et al, 2007;Kreuter et al, 2010;Dahlstrom, 2014) and more acceptable for patients with low and adequate health literacy (Moran et al, 2016) and populations that had a strong oral tradition (Hinyard and Kreuter, 2007), such as Indonesia. It is noteworthy to mention that PERANTARA contained information about both medical and psychosocial issues related to BC symptoms and diagnosis procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Again, while many communities recognize the importance of hygienic practices, studies suggest limited observance of these practices. Research within risk communication suggests that the effectiveness of health messages to change attitudes and practices can be enhanced when risks are communicated in narrative or story formats, especially within low-health-literacy populations (Goddu et al 2015;Moran et al 2016). Narrative messages embed health information "within a representation of connected events and characters that has an identifiable structure, is bounded in space and time and contains explicit or implicit messages about the topic being addressed" (Kreuter et al 2007, p. 222).…”
Section: Narrative Risk Messages To Promote Behavioural Changementioning
confidence: 99%
“…Of the 18 films in the company's collection, four films utilised a narrative format and 14 films adopted a non-narrative format. While a non-narrative format can present information directly to viewers, health information woven into a narrative or story may be more useful for learning, particularly in low health literacy populations (Moran et al, 2016). Given that the production company is seeking to produce more narrative-based films, principles of anchored instruction may provide a useful framework to encourage viewers to critically engage with and discuss the depicted content, potentially equipping them with a tool to formulate solutions to the health issues affecting the contexts in which they live and work (Bransford et al, 1990).…”
Section: Producing Community Health Education Films: Production Phasementioning
confidence: 99%